A systematic approach of rock slope stability assessment: a case study at Gunung Kandu, Gopeng, Perak, Malaysia - Ainul Mardhiyah Mohd Razib,; Goh, Thian Lai; Nur Amanina Mazlan,; Muhammad Fahmi Abdul Ghani,; Tuan Rusli Tuan Mohamed,; Abdul Ghani Rafek,; Ailie Sofyiana Serasa,; Chen, Yanlong; Zhang, Mingwei (Penerbit Universiti Kebangsaan Malaysia, 2018)
The stability of the limestone cliff at Gunung Kandu, Gopeng, Perak, Malaysia was assessed based on the Slope Mass Rating (SMR) system on 53 cross sections of the Gunung Kandu hill slopes. The slopes of Gunung Kandu were identified as class I (very good) to IV (poor). The kinematic analysis showed that 12 out of 53 hill slopes of Gunung Kandu were identified as having potential wedge, planar and toppling failures. The assessment showed that the stability of the western flanks can be classified as stable to unstable with the probability of failure from 0.2 to 0.6. The stability of the eastern and southern flanks range from very stable to partially stable with the probability of failure from 0.0 to 0.4. While the stability of northern flanks are from very stable to stable with the probability of failure of 0.0 - 0.2. This systematic approach offers a practical method especially for large area of rock slope stability assessment and the results from probability of failure values will help engineers to design adequate mitigation measures.